A Multi-Epitope Fusion Protein-Based p-ELISA Method for Diagnosing Bovine and Goat Brucellosis - Yin, Dehui; Bai, Qiongqiong; Wu, Xiling; Li, Han; Shao, Jihong; Sun, Mingjun; Zhang, Jinpeng (Frontiers in Veterinary Science, 2021)
In recent years, the incidence of brucellosis has increased annually, causing tremendous economic losses to animal husbandry in a lot of countries. Therefore, developing rapid, sensitive and specific diagnostic techniques is critical to control the spread of brucellosis. In this study, bioinformatics technology was used to predict the B cell epitopes of the main Brucella out membrane proteins, and the diagnostic efficacy of each epitope was verified by indirect enzyme-linked immunosorbent assay (iELISA). Then, a fusion protein containing 22 verified epitopes were prokaryotically expressed and used as antigen in paper-based ELISA (p-ELISA)for serodiagnosis of brucellosis. The multiepitope based p-ELISA was evaluated using a collection of brucellosis positive and negative sera collected from bovine and goat respectively. Receiver operating characteristic (ROC) curve analysis showed that the sensitivity and specificity of detection-ELISA in diagnosing goat brucellosis were 98.85% and 98.51%. The positive and the negative predictive value was 99.29% and 98.15% respectively. In diagnosing bovine brucellosis, the sensitivity and specificity of this method were 97.85% and 96.61%, with positive and the negative predictive value being identified as 98.28% and 97.33% respectively. This study demonstrated that the B cell epitopes contained in major antigenic proteins of Brucella can be a very useful antigen source in developing highly sensitive and specific method for serodiagnosis of brucellosis.